2013
DOI: 10.1371/journal.pone.0053185
|View full text |Cite
|
Sign up to set email alerts
|

Frontalis Muscle Flap Suspension for the Correction of Congenital Blepharoptosis in Early Age Children

Abstract: BackgroundWe aimed to report our successful use of frontalis muscle flap suspension for the correction of congenital blepharoptosis in early age children.MethodsThis retrospective study included 61 early age children (41 boys, 20 girls) with an average age of 6 years (range, 3–10 years) with congenital blepharoptosis who received surgery during the period from March 2007 to January 2011. There were 39 cases of unilateral blepharoptosis and 22 cases of bilateral blepharoptosis, thus a total of 83 eyes were affe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 21 publications
(35 reference statements)
0
12
0
Order By: Relevance
“…(19). In recent years, there have been publications about the use of a frontal muscle flap, with its own blood supply and innervation, which is directly connected to the eyelid and provides its opening without the need of implants or autologous transplants (21,22). In our case of traumatic paralytic ptosis, we used a combined technique of maximum levator resection and modified front suspension with frontal muscle flaps and fascia.…”
Section: Discussionmentioning
confidence: 99%
“…(19). In recent years, there have been publications about the use of a frontal muscle flap, with its own blood supply and innervation, which is directly connected to the eyelid and provides its opening without the need of implants or autologous transplants (21,22). In our case of traumatic paralytic ptosis, we used a combined technique of maximum levator resection and modified front suspension with frontal muscle flaps and fascia.…”
Section: Discussionmentioning
confidence: 99%
“…Hou et al 11 suggested that the height of the lateral fixation point should be higher than that of the midpoint to obtain a natural curvature in frontalis muscle flap suspension surgery for the correction of congenital ptosis. The concept of the functional eyelid centre could explain why the fixation point would be better placed slightly laterally in these studies.…”
Section: Discussionmentioning
confidence: 99%
“…Congenital blepharoptosis is most frequently associated with an idiopathic dystrophy of the levator palpebrae superioris muscle (Hou et al 2013;Hoyt and Taylor 2013;Kanski and Bowling 2013). Other theories propose absent muscle development due to a failure of neuronal migration as the cause behind the ptosis (McMullan and Tyers 2001).…”
Section: Orientation and Length Of The Palpebral Fissuresmentioning
confidence: 99%